The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1136/heart.86.2.183
|View full text |Cite
|
Sign up to set email alerts
|

Incremental shuttle walk test in the assessment of patients for heart transplantation

Abstract: Objective-To compare the incremental shuttle walk test (ISWT) with treadmill exercise testing (TT) derived measurement of peak oxygen consumption (peak VO 2 ) in patients undergoing assessment for cardiac transplantation. Design-Prospective comparison. All investigations occurred during a single period of admission for transplant assessment. Setting-Single UK cardiothoracic transplantation unit. Patients-25 patients recruited (21 men). Mean age was 53 years. Interventions-Patients underwent two TT of peak VO 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
4
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 15 publications
5
34
4
1
Order By: Relevance
“…In a larger placebo-controlled trial, Malkin et al (9) found that a 12-month testosterone replacement therapy improved both distance walked at the shuttle walking test and forearm muscle strength in men with moderately severe CHF. Assessment of exercise capacity by means of effort tolerance tests such as the 6MWT and incremental shuttle walk test is easy to perform, correlates with peak VO 2 , and has been shown to be useful in prognostic stratification (27)(28)(29)(30). However, these assessments do not reflect the overall cardiovascular performance (30) and do not provide any information as to the ventilatory efficiency and cardiopulmonary matching during exercise, which play a relevant pathophysiological and prognostic role in CHF (11,12,30,31).…”
Section: Discussionmentioning
confidence: 99%
“…In a larger placebo-controlled trial, Malkin et al (9) found that a 12-month testosterone replacement therapy improved both distance walked at the shuttle walking test and forearm muscle strength in men with moderately severe CHF. Assessment of exercise capacity by means of effort tolerance tests such as the 6MWT and incremental shuttle walk test is easy to perform, correlates with peak VO 2 , and has been shown to be useful in prognostic stratification (27)(28)(29)(30). However, these assessments do not reflect the overall cardiovascular performance (30) and do not provide any information as to the ventilatory efficiency and cardiopulmonary matching during exercise, which play a relevant pathophysiological and prognostic role in CHF (11,12,30,31).…”
Section: Discussionmentioning
confidence: 99%
“…In more severe CHF patients, baseline 6-MWT distance was a strong independent predictor of mortality and hospitalisation at 1 yr [235]. The feasibility of the SWT for selection for heart transplantation has been documented; a distance of .450 m equates to a V9O 2 ,peak for treadmill walking .14 mL?min -1 ?kg -1 [236].…”
Section: Walking Testsmentioning
confidence: 99%
“…Patients performed a practice ISWT beforehand to minimise the influence of learning effects. Participants were asked to walk for as long as possible until reaching test termination criteria while the assessor recorded the total number of shuttles performed 13 . The ISWT has been validated against VO 2 max and VO 2 peak in clinical populations 14 .…”
Section: Physical Function Measurementsmentioning
confidence: 99%